Early Postoperative Magnetic Resonance Imaging Findings After Autologous Osteochondral Plug Grafts For Osteochondritis Dissecans of the Humeral Capitellum. Issue 7 (18th July 2016) - Maruyama, Masahiro; Takahara, Masatoshi; Harada, Mikio; Satake, Hiroshi; Uno, Tomohiro; Takagi, Michiaki
Objectives: Although good clinical outcomes of autologous osteochondral plug grafts for capitellar osteochondritis dissecans (OCD) have been reported, the timing of return to sports was various and still controversial. The period of graft incorporation and the lesion healing at repair site is important to establish the rehabilitation protocol, however there is little information. The aim of this study was to investigate early postoperative magnetic resonance imaging (MRI) findings and clinical outcomes after autologous osteochondral plug grafts for capitellar OCD. Methods: Fifteen young baseball players with advanced lesions of capitellar OCD underwent a procedure using autologous osteochondral plug grafts and underwent MRI (1.5 T) scan at 3 and 6 months, postoperatively. Their mean age at the time of surgery was 13.5 years (range, 13-15 years). Four lesions were classified as International Cartilage Repair Society (ICRS) OCD III and 11 lesions as OCD IV. The mean size of the lesions (sagittal × coronal) was 16 × 14 mm and the mean surface area was 181 mm2. One to two osteochondral plug grafts, with a mean diameter of 7 mm (range, 6-8 mm), were harvested from the lateral femoral condyle and transplanted to the defects. The mean reconstruction rate was 41% (range, 12%-65%), which was calculated as (total surface area of the grafts × 100%)/ (surface area of the lesion). Patients were allowed to begin throwing after 3 months and to return to sports after 6 months. The mean follow-up was 21 months (range, 12-36 months). The MRI findings were assessed graft incorporation, which was indicated by no T1-low-signal-intensity at the graft and no fluid surrounding the graft on T2-weighted fat-suppression (Figure 1), and the lesion healing according to the scoring system of Henderson (4, complete healing; 16, no healing). MRI were blinded and randomized, and two observers reviewed independently and conferred when they differed. Clinical outcomes were evaluated as elbow pain, Timmerman and Andrews (T&A) scores, and return to baseball. We also analyzed the relationship between complete healing at 6 months and each factor: graft size, lesion size, reconstruction rate. Results: Grafts were incorporated in 11 patients at 3 months and 13 patients (87%) at 6 months, postoperatively (Table 1). Mean Henderson score were 4.6 at 3 months and 4.5 at 6 months, and complete healing was in 9 patients at 3 months and 11 patients (73%) at 6 months. The mean T&A score improved significantly from 141 to 184 (P < .05). Thirteen patients had no elbow pain and one patient had occasional mild throwing pain, and all these patients (93%) returned to a competitive level at 6 months. The remaining one patient whose reconstruction rate was 24% and MRI showed incomplete healing at 6 months was difficult to throw because of elbow pain and underwent revision surgery. There were no relationships between complete healing and graft or lesion size (mean graft size: complete 7.4 mm, incomplete 6.8 mm, P = .16, mean lesion size: complete 166 mm2, incomplete 220 mm2, P = .13). On the other hand, all nine patients whose reconstruction rate was 36% or more were achieved complete healing, whereas two of six patients (33%) less than 36% did (P < .05). Conclusion: These results indicated that our rehabilitation protocol was appropriate for young baseball players after autologous osteochondral plug grafts for capitellar OCD. Although it is not clinically required to reconstruct the entire articular defect, more than 36% of the area should be reconstructed.